(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The hip fracture feels pain next to the femur and pelvis and has difficulty walking. After hip fracture, side effects can occur throughout the whole body including ulcer, pneumonia, and hematocardial thrombosis. Therefore, this study is the optimal experimental effect of clinical information management to prevent complications in patients with hip joint surgery. Experimental group of 83 patients which was assigned as group with intervention, while the control group of 83 patients was assigned as group without intervention. The comparison of dietary behavior and physical condition after the application of clinical information management was analyzed as t-test. The results of this study are as follows. Firstly, muscle strength after hip joint surgery has been strengthened after management than before health management (t=-4.15, p<.01). Secondly, after hip joint surgery, complications decreased significantly to 30-40% after training compared to pre-health management(t=-8.13, p<.01). Therefore, clinical information management has proven effective in reducing complications after hip joint surgery.